2018
DOI: 10.1002/jso.25085
|View full text |Cite
|
Sign up to set email alerts
|

The association between preoperative serum interleukin‐6 levels and postoperative prognosis in patients with T2 gallbladder cancer

Abstract: Preoperative serum IL-6 is significantly associated with prognostic implications in patients with hepatic side T2 GBC, not in those with peritoneal side tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Serum CA19-9 is the most evaluated prognostic biomarker in BTC and our data support the prognostic association, especially as a continuous variable prior to treatment. However, serum IL6 has previously been proposed to be associated with tumor burden and DFS (30,40,41), and IL6 and YKL-40 have been associated with OS in small studies of BTC (28,29,31), as well as in the larger ABC-03 trial for IL6 (32). Our results indicate a possible clinical utility of these inflammatory biomarkers measured at inclusion either in combination with CA19-9 or, in the case of IL6, providing warranted prognostic information in patients with BTC with normal levels of CA19-9.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CA19-9 is the most evaluated prognostic biomarker in BTC and our data support the prognostic association, especially as a continuous variable prior to treatment. However, serum IL6 has previously been proposed to be associated with tumor burden and DFS (30,40,41), and IL6 and YKL-40 have been associated with OS in small studies of BTC (28,29,31), as well as in the larger ABC-03 trial for IL6 (32). Our results indicate a possible clinical utility of these inflammatory biomarkers measured at inclusion either in combination with CA19-9 or, in the case of IL6, providing warranted prognostic information in patients with BTC with normal levels of CA19-9.…”
Section: Discussionmentioning
confidence: 99%
“…[109,110] serum IL-6 ECLIA Low levels correlated with a better 5-year overall survival rate in a subgroup of patients with hepatic side tumors (n = 69). [111] preoperative NLR Hemogram…”
Section: Molecular Prognostic Biomarkersmentioning
confidence: 99%
“…A total of 27 studies 9 , 10 , 17 , 23 , 28 33 , 35 , 37 , 38 , 40 44 , 46 , 49 , 50 , 52 57 with 10 164 cases were incorporated. Pooled results indicated that poorly differentiated tumor was a risk factor for OS among resected cases with GBC (HR=3.22, 95% CI: 1.65–2.87, P <0.00001) (Figure S1J, Supplemental Digital Content 4, http://links.lww.com/JS9/C302 ) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3 studies 50 , 52 , 55 with 617 cases were incorporated. Pooled results indicated that hepatic tumor shared more worse prognosis than peritoneal tumor and tumor location (peritoneal side vs hepatic side) was a prognostic factor for resected GBC (HR=1.85, 95% CI: 1.51–2.28, P <0.00001) (Figure S1L, Supplemental Digital Content 4, http://links.lww.com/JS9/C302 ) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%